Development of interactive powerpoint learning media based on information and communication technologies to improve student learning outcomes - Setiawan, Angga; Nugroho, Wahyu; Widyaningtyas, Dessy; Nugroho, Nugroho (Universitas Nusantara PGRI Kediri, 2023)
Research conducted by researchers on the development of interactive PowerPoint learning media based on Information And Communication Technologies is based on conceptual and theoretical understanding using thematic learning that is felt to be not fully understood by students, this has resulted in decreased student learning outcomes. To solve problems in the learning process, learning media is needed. The purpose of this research is to implement the development of interactive PowerPoint media using ICT for fifth-grade students of SDN 1 Gamping. This media was developed in the form of several slides which are equipped with buttons that are inserted by hyperlinks in the learning menu so that it will make it easier for the user to go to the slide after the specified slide. This study used the ADDIE research model as a development model. The research findings showed an average material validity score of 80% (appropriate), an average language validity score of 92% (very feasible), and an average media validity score of 88% (very feasible). Calculation of media effectiveness based on n-gain obtained a score of 0.59 in the medium category. Responses to ICT-based interactive PowerPoint learning media were obtained from small-scale tests with an average score of 80% while field-scale tests obtained an average value of 86%, overall Student responses related to media can be said to be positive. So that the analysis data obtained states that ICT-based interactive PowerPoint learning media is effective in improving student learning outcomes.